2020
DOI: 10.3390/ijerph17207502
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Smoke-Free Home Rules and Exposure to Secondhand Smoke in Poland: A National Cross-Sectional Survey

Abstract: Smoke-free policies have been shown to significantly reduce secondhand smoke (SHS) exposure in private and public places. The objectives of this study were to: (1) to assess the prevalence and characteristics of voluntary smoke-free home rules in Poland; and (2) assess the association of smoke-free rules with self-reported SHS exposure in private homes. A cross-sectional survey was conducted in September 2019 with a nationally representative sample of 1011 individuals aged 15 and over. Nationally, 66.1% of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 23 publications
0
31
2
Order By: Relevance
“…The prevalence of strict home smoking bans in the current report (42.0%) was lower than prior studies’ prevalence, with the enforcement of voluntary strict home smoking bans reported to be 61% in homes in Italy 38 , 50% in homes in the United States 35 , and 66.1% in homes in Poland 39 . Similarly, a study based on data from four countries, namely, Canada (67.8%), the United States (60.2%), England (59.2%), and Australia (66.2%), reported higher prevalence of strict home smoking bans than our study 40 .…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…The prevalence of strict home smoking bans in the current report (42.0%) was lower than prior studies’ prevalence, with the enforcement of voluntary strict home smoking bans reported to be 61% in homes in Italy 38 , 50% in homes in the United States 35 , and 66.1% in homes in Poland 39 . Similarly, a study based on data from four countries, namely, Canada (67.8%), the United States (60.2%), England (59.2%), and Australia (66.2%), reported higher prevalence of strict home smoking bans than our study 40 .…”
Section: Discussioncontrasting
confidence: 83%
“…Moreover, we observed that younger parents aged 18–34 years were less likely to implement a strict home smoking rule than older parents. This observation of an association between age and implantation of a smoke-free home rule was not observed in prior studies 23 , 39 . Furthermore, our results illustrated that subjects who received higher education (i.e.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…This study showed that more than half of respondents were not concerned about the harmful effect of passive smoking on their health. It is estimated that only two-thirds of the Polish population has adopted a total smoke-free home rule [30]. Despite the implementation of the smoking ban in most public places, 11.7% of adults in Poland are exposed to secondhand smoke in public transport stops and facilities, and 6.7% are exposed to secondhand smoke in the workplace [30].…”
Section: Discussionmentioning
confidence: 99%